Pengaruh Pelatihan Terhadap Kinerja Sumber Daya Manusia - Lina Priliana; Ahmad Gunawan (Jurnal Ekonomi dan Bisnis Digital, 2023)
Every organization requires quality Human Resources (HR), creating quality Human Resources (HR) through training. Training is directed at maintaining and improving the job performance of employees in an organization. Training is related to efforts to improve the practical skills and abilities needed to carry out work effectively. Basically, training is needed because there is a gap between the skills of current workers and the skills needed to occupy new positions. The purpose of this research is to determine the effect of training on the performance employees of PT. Batam. Based on the results of research discussions conducted at PT. Batam entitled the effect of training on the performance employees of PT. Batam.